2008
DOI: 10.1002/gps.2080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of APOE status on cognitive maintenance in healthy elderly persons

Abstract: The epsilon4 allele of the ApoE gene has a negative impact on cognitive performance, notably on episodic memory functions, in physically and mentally healthy aged persons. Practice effects seen in carriers of the ApoE epsilon4 were inferior in most areas tested to the effects seen in ApoE epsilon4 non-carriers. Further follow-up of these subjects will help to determine the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
(45 reference statements)
1
30
2
Order By: Relevance
“…Additionally, Martin and colleagues [3] conducted a systematic review of the cognitive training intervention effects on various cognitive functioning domains (i.e., memory, EF, attention, and processing speed), finding that, versus a non-treatment control condition, cognitively intact older adults receiving cognitive training significantly improved their immediate and delayed verbal recall scores. Our results also contradict those obtained by Zehnder et al [45], which indicated that practice effects in APOE 4 allele carriers were inferior in most tested areas compared to the effects found in the noncarriers, especially in episodic memory functions (immediate verbal learning and delayed recall).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, Martin and colleagues [3] conducted a systematic review of the cognitive training intervention effects on various cognitive functioning domains (i.e., memory, EF, attention, and processing speed), finding that, versus a non-treatment control condition, cognitively intact older adults receiving cognitive training significantly improved their immediate and delayed verbal recall scores. Our results also contradict those obtained by Zehnder et al [45], which indicated that practice effects in APOE 4 allele carriers were inferior in most tested areas compared to the effects found in the noncarriers, especially in episodic memory functions (immediate verbal learning and delayed recall).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, they observed that the noncarriers in the cognitively healthy NDFAM group benefited from CS, as evidenced by improved cognitive performance (particularly, in visuospatial memory function), whereas the APOE 4 carriers showed no significant improvement. Finally, a study carried out by Zehnder et al [45] measured the practice effect on cognitive performance by applying two neuropsychological assessment instruments in physically and mentally cognitively intact aged people (with a mean age of 70 years): initially at baseline and then, two years later. Their results indicated that the 4 allele of the APOE gene had a negative impact on cognitive performance, notably on episodic memory tasks (such as immediate verbal learning and delayed recall).…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime risk of AD at the age of 85 years without reference to APOE genotype is about five-fold lower than that for ApoE 4 carriers [57]. Moreover, APOE 4 possession is associated with earlier and faster cognitive decline in patients with AD [58], and may impact cognitive performance, notably episodic memory functions, in cognitively healthy aged persons [59]. APOE-status is therefore a critical selection and matching variable in longitudinal studies of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more than a decade of research has also demonstrated deficits in various cognitive domains in non-demented ɛ4 carriers in comparison with non-ɛ4 carriers in middle and old adulthood (e.g., Berr et al, 1996;Cantu, 2000; De Blasi et al, 2009;Driscoll, McDaniel, & Guynn, 2005;Greenwood, Lambert, Sunderland, & Parasuraman, 2005;Helkala et al, 1995;Lavretsky et al, 2003;Negash et al, 2007; Packard et al, 2007;Reed et al, 1994;Small et al, 1999;Wetter et al, 2005;Zehnder et al, 2009). …”
Section: Discussionmentioning
confidence: 99%